Optimized dynamical control of state transfer through noisy spin chains - Zwick, Analía Elizabeth (2014)
We propose a method of optimally controlling the tradeoff of speed and fidelity of state transfer through a noisy quantum channel (spin-chain). This process is treated as qubit state-transfer through a fermionic bath. We show that dynamical modulation of the boundary-qubits levels can ensure state transfer with the best tradeoff of speed and fidelity. This is achievable by dynamically optimizing the transmission spectrum of the channel. The resulting optimal control is robust against both static and fluctuating noise in the channels spin-spin couplings. It may also facilitate transfer in the presence of diagonal disorder (on site energy noise) in the channel.